The role of Muslim faith-based programs in transforming the lives of people suffering with mental health and addiction problems. (1st November 2016) - Jozaghi, Ehsan; Asadullah, Muhammad; Dahya, Azim
Abstract: Many countries have trouble addressing the dual problems of mental health and addiction because of their extremely conventional health care models. This is particularly true of the refugees and immigrant populations who are often part of religious minorities. The current study is based on qualitative, in-depth interviews with eight faith-based program volunteers. NVivo 10 was used to facilitate coding and analysis. The findings underscored the role of a faith-based project in making noticeable contributions that reduce the traditional stigma attached to addictions and mental health problems. This is the first study in Canada to particularly highlight addictions and mental health issues tackled by Muslims within their own community, and we capture the opinion of both practitioners and experts. As such, we build a foundation for future research in the field of substance use, harm reduction, and mental health issues in the Muslim community.